Mastectomized women primary caregiver’s abilities. - Ostiguín Meléndez, Rosa María; Rivas Herrera, José Cruz; Vallejo Allende, Maite; Crespo Knopfler, Silvia; Alvarado Aguilar, Salvador (Investigación y Educación en Enfermería, 2025)
Objective. To describe the abilities in care, mastectomized women primary caregivers (PC) have, in terms of knowledge, value and patience. Methodology. Cross sectional descriptive study carried out in 2010 in the National Institute of cancerology in Mexico City. A sample of 100 primary caregivers was used. For the abilities measurement the instrument “caring abilities inventory”, which has 3 subscales, Knowledge, value and patience, was used. Correlations were estimated among the sum of the terms comparing them with the sociodemographic variables. Results 41% of the PC were men, 77% were married, 41% were the patient’s children and 32% their couple, most of them had a paid job. Caregivers mean age was 43 years. Regarding caregiver abilities a high score for the dimensions knowledge and patience, and a low score for value was found. The correlation between value and patience was low. Conclusion. The most important abilities caregivers must have are knowledge and patience. Value didn’t show such relevance.